Produk Interior Fasilitas Publik di Yello Hotel Dengan Bahan Rotan - Nerissa Arviana Wijaya (Intra, 2017)
Indonesia is one of the largest rattan producers in the world and needs to be developed because it has ecological, economic and cultural value. Seeing the increasing growth of hotels especially in Surabaya, rattan can be utilized as an interior product of the hotel to be developed. One of the hotels that has unique characteristics in Surabaya is Hotel Yello with a yellow interior atmosphere. The design method used is the Zeisel method of data collection, programming, initial design, design development, final design, evaluation. Products that are designed are bench, table and standing lamp. Design concept inspired from the formation in accordance with the characteristics of rattan, natural color finishing rattan and the atmosphere of space Yello Hotel. Concept applications on the product are in the formation that is curved with yellow and brown finishing, the holder is colored yellow.